Optimalisasi Poskestren Al-Hidayah, Sidoarjo dengan deteksi tumbuh kembang dan pembentukan kader Remaspro (Remaja Sadar Kesehatan Reproduksi) - Rahayu, Esty Puji; Nisa, Fauziyatun; Dwi Andriani, Ratna Ariesta; Delina, Lini (Journal of Dedicators Community, 2023)
Background, Many problems are experienced by adolescents especially adolescent women, for example, nutritional problems, anemia, menstruation, lack of concentration in learning and others. This does not rule out the possibility of also being experienced by female students in Islamic boarding schools. One way to improve the understanding of reproductive health and sexuality can be by optimizing poskestren (Pesantren Health Post). The purpose of this community service is to optimize the Al Hidayah Poskestren with Remaspro cadres and monitor the growth and development of female students by providing reproductive health education. Mitra is located on the outskirts of Sidoarjo district. The number of female students in the Pesantren is approximately 230 people, while the existing Poskestren is not optimal and the place is inadequate. This pesantren is also a pesantren that does not maintain the cleanliness of the environment, starting from the place to dry clothes, canteens, rooms, bathrooms and poskestrennya itself. In Poskestren, there are also no administrators or cadres who deal with reproductive problems, because reproductive and sexuality problems are indeed considered taboo and are not studied in depthMethods: In this community service we provide education and train remaspro cadres about adolescent reproductive health and all its problems, train remaspro cadres about physical examinations focused on adolescents (early detection of anemia), conduct Hb level examinations, form the management of Poskestren. The appointed Remaspro cadres are also the administrators of the Poskestren, which numbers 24 female students. After that, counseling was carried out to all students about menstruation, adolescent nutritional status, and adolescent personal hygiene. Results and discussion. Based on the results of the Hb level examination, there were adolescents who were anemic, around 12.6% of adolescents had anemia. Based on interviews with teenagers who have anemia, they said that during the examination, they were menstruating, besides that they also stated that they did not like vegetables.Conclusion. Based on the results of monitoring and evaluation after the implementation of community service, it can be concluded that there is an increase in knowledge about menstruation, adolescent nutrition and anemia in adolescents. Further activities can develop Poskestren activities, for example peer teaching about juvenile delinquency and the dangers of cigarettes in students